Chemical Characterization, Antioxidant and Cytotoxic Activities of the Edible Fruits of Brosimun gaudichaudii Trécul, a Native Plant of the Cerrado Biome. Issue 7 (14th June 2021) - Mickely W. Engelbrecht, Luma; Vicente Ribeiro, Reginaldo; Cristiane Yoshida, Nídia; dos Santos Gonçalves, Valéria; Pavan, Eduarda; Tabajara de Oliveira Martins, Domingos; Luiz dos Santos, Érica
Abstract: In Brazil, there is a large diversity of species of small edible fruits that are considered sources of nutrients and functional properties. They present a high innovation domain for the pharmaceutical, cosmetic and food industries due to their health‐promoting properties. Edible fruits from Brosimum gaudichaudii (Moraceae) are widely consumed and used in folk medicine and in feed by the population of the Brazilian Cerrado. Nevertheless, detailed information on the chemical fingerprint, antiradical activity and safety aspects of these fruits is still unknown. Thus, the aim of this work was to investigate the bioactive compounds of hydroethanolic extracts of fruits from Brosimum gaudichaudii using high‐performance liquid chromatography combined with mass spectrometry using electrospray ionization (HPLC ESI‐MS). Eighteen different compounds, including flavonoids, coumarins, arylbenzofurans, terpenoids, stilbenes, xanthones and esters, were detected. Moreover, the study indicated that the hydroethanolic extract of fruits from B. gaudichaudii presented low scavenging activity against 2, 2‐diphenyl‐1‐picrylhydrazyl radicals (IC50 >800 μg mL −1 ) and was cytotoxic (IC50 <30 μg mL −1 ) in Chinese hamster ovary cells (CHO−K1) by an in vitro assay. This is the first report of the chemical profile, antioxidant activity and cytotoxic properties of the hydroethanolic extract of fruits from B. gaudichaudii . Abstract :